2014
DOI: 10.1186/2052-336x-12-77
|View full text |Cite
|
Sign up to set email alerts
|

Oily wastewaters treatment using Pseudomonas sp. isolated from the compost fertilizer

Abstract: BackgroundDischarging the oily wastewater in the environment causes serious problems, because of the oil compounds and organic materials presence. Applying biological methods using the lipase enzyme producer microorganisms can be an appropriate choice for treatment of these wastewaters. The aim of this study is to treat those oil wastewaters having high concentration of oil by applying lipase enzyme producer bacteria.Materials and methodsOil concentration measurement was conducted using the standard method of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 18 publications
1
14
0
2
Order By: Relevance
“…After each cycle and before its reuse, the lipase was filtered out, rinsed, and finally dried. Although the activity of the immobilized enzyme began to decrease after five cycles, more than 55% of its original activity was retained even after 10 cycles, which is comparable with the literature (Figure ). In contrast, the activity loss was critical after 15 cycles showing that the immobilized enzyme activities decreased with continued use.…”
Section: Resultssupporting
confidence: 91%
“…After each cycle and before its reuse, the lipase was filtered out, rinsed, and finally dried. Although the activity of the immobilized enzyme began to decrease after five cycles, more than 55% of its original activity was retained even after 10 cycles, which is comparable with the literature (Figure ). In contrast, the activity loss was critical after 15 cycles showing that the immobilized enzyme activities decreased with continued use.…”
Section: Resultssupporting
confidence: 91%
“…There are several soil-cleaning methods to reduce toxicity and hazards of environment, including incineration (burning), washing, chemical applying, land filling, and bioremediation (Azhdarpoor et al 2014;Martínez et al 2000). However, these removal or treatment technologies except bioremediation have been found to have inherent drawbacks owing to their tendency to form secondary toxic intermediates and also proven to be costly (Mohsenzadeh et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The thermophilous fungi that grow at about 50°C are in charge for lignin degradation (Tuomela et al, 2000). Some promising strategies to produce compost from olive oil wastes by using different microbes have been reported (Azhdarpoor et al, 2014;Fernández-Hernández, García-Ortiz Civantos, Roig, & Sánchez-Monedero, 2013). Toscano, Casacchia, Diacono, and Montemurro (2013) observed that after soil application of composted olive mill by-products olive yields increased on average by 9% compared to the untreated soils.…”
Section: Compostingmentioning
confidence: 98%
“…The composting of olive mill wastes have been shown to be a feasible method of producing mature, pathogen-free compost, ensuring maximum benefit for crop production (Azhdarpoor, Mortazavi, & Moussavi, 2014;Federici et al, 2011;Tortosa, Alburquerque, Ait-Baddi, & Cegarra, 2012;Tortosa, Alburquerque, Bedmar, Ait-Baddi, & Cegarra, 2014). Different groups of microorganisms participate in the composting process depending on the temperature of the composting mass (Keener, Dick, & Hoitink, 2000).…”
Section: Compostingmentioning
confidence: 99%